2022
DOI: 10.1097/sla.0000000000005601
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Distal Pancreatectomy

Abstract: Background and Objective: Robotic distal pancreatectomy (DP) is an emerging attractive approach, but its role compared with laparoscopic or open surgery remains unclear. Benchmark values are novel and objective tools for such comparisons. The aim of this study was to identify benchmark cutoffs for many outcome parameters for DP with or without splenectomy beyond the learning curve. Methods: This study analyzed outcomes from international expert centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Meanwhile, adequate case selection with regards to favourable anatomical (low BMI) and disease specific (no vessel involvement) features in a first learning phase under supervision to reach competency level seems of paramount importance. With increasing experience, proficiency and mastery levels are reached and more complex procedures may be introduced with the goal to achieve benchmark outcomes 28 , 38 . Furthermore, several initiatives for collaborative research on safe implementation of the minimally invasive technique in pancreatic surgery, such as the European Consortium of Minimally Invasive Pancreatic Surgery (E-MIPS), have emerged 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, adequate case selection with regards to favourable anatomical (low BMI) and disease specific (no vessel involvement) features in a first learning phase under supervision to reach competency level seems of paramount importance. With increasing experience, proficiency and mastery levels are reached and more complex procedures may be introduced with the goal to achieve benchmark outcomes 28 , 38 . Furthermore, several initiatives for collaborative research on safe implementation of the minimally invasive technique in pancreatic surgery, such as the European Consortium of Minimally Invasive Pancreatic Surgery (E-MIPS), have emerged 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“… 6 , postoperative safety outcomes from the current meta-analysis appear within benchmark cut-offs. Recently published analyses further report benchmark criteria for minimally invasive and open DP 38 , 43 , 44 . Benchmark cut-off values for mortality rate in PD were set at less than or equal to 1.6 per cent and 2 per cent by Sánchez-Velázquez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies based on the data analysis of multicentre and large-scale studies reported the benchmark values of MIDP to identify the best achievable results and define optimal perioperative outcomes, with the intention of assessing and enhancing the surgery quality [ 65 , 66 ]. Muller et al [ 66 ] reported that benchmark values of RDP included: operation time ≤ 300 min, estimated blood loss ≤ 150 ml, conversion rate ≤ 3%, major complication rate ≤ 26.7%, clinical pancreatic fistula rate ≤ 32%, lymph node retrieval for PADC ≥ 9, and R0 resection rate for PDAC ≥ 83%. In the majority of the included studies, there was a disparity between the outcomes and the benchmark values.…”
Section: Discussionmentioning
confidence: 99%
“…18 The research group of Clavien et al introduced the notion of global outcome benchmarks, where procedure-specific outcome goals are set for a list of clinically relevant quality indicators (QIs), based on the 75th percentile of the outcomes obtained in international high-volume centers. 11,13,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] Global outcome benchmarks have been so far established for minimally invasive esophagectomy, 25 liver surgery, 26 liver transplantation, 24,31 ALPPS (associating liver partition and portal vein ligation for staged hepatectomy), 22 pancreatic surgery, 20,23 colorectal resections, 32 as well as for bariatric surgery 19,21 (►Table 1). Meanwhile, Kolfschoten et al developed a composite outcome measure representing the percentage of patients with textbook outcomes, meaning that all desired health outcomes are reached simultaneously.…”
Section: Ideal Surgical Outcomesmentioning
confidence: 99%